Texts, Transmissions, Receptions - Lardinois, A. (Radboud Studies in Humanities, 2015)
The papers collected in this volume study the function and meaning of various kinds of narrative texts from the perspective of New Philology, Linguistics, Iconography and Reception studies. Their purpose is to understand the workings of narrative texts.